Current Situation and Future Perspectives of the Romanian Renewable Energy - Ştefan Dragoş Cîrstea; Claudia Steluţa Martiş; Andreea Cîrstea; Anca Constantinescu-Dobra; Melinda Timea Fülöp (Energies, 2018)
In 2015, Romania was the first country in Europe that achieved EU targets regarding the share of renewables in the generation mix, far ahead of the 2020 deadline. Starting with the energy structure in Romania, the paper: (1) analyses the evolution of the main indicators in the renewable energy sector, (2) discloses the perspectives of renewable energy in Romania synthesizing the main trends of development in the field, and (3) analyses the challenges facing with the development of renewable energy in Romania. Based on analyzing the exploratory data, the paper makes a preliminary prediction of the development of the sector for future decades and proposes targeted countermeasures and suggestions. Romania still has unexploited potential concerning renewable energy sources. Since Romania registered continuous economic growth, the demand for electricity is steadily growing, and this trend is expected to continue. Additionally, Romania could introduce a support mechanism for developing the potential of unexploited existing resources. The results of the present study may be useful for further research regarding public policies for the development of renewable energy. Furthermore, it can represent a useful analysis in order to identify future trends of renewable energy in Romania.